Aplikasi Perhitungan PPn Atas Jasa Pihak Ketiga - Rinata Adityanti; Ali Mulyawan (Jurnal Computech & Bisnis (e-Journal), 2015)
This research aims to design a system thati in order to make a calculation of salaries and VAT application on 3rd party. Currently the data processing is still done manually which caused some problems as well as constraints such as lack of proper calculation that takes a long time in the process poses, so it needs to be made an application that can handle these problems. To achieve these objectives need to be done in the following steps of conducting systems analysis, design and implement the payroll calculation application and Vat on 3rd party services using Microsoft Visual Sttudio 2005 (VB.Net) as media processing. Through this system is expected to support to facilitate the process.Keywords: calculation of salaries and Vat, PT. KAI, VB.Net  Keywords: waterfall;  VAT application